Psychological criminology: an integrative approach - Wortley, Richard (Crime science series, 2024)
"Psychological Criminology explores what is it about individuals and their experiences that cause them to commit crime and or to become criminal. Fully updated to include the latest theories and research, this new edition provides comprehensive coverage of psychological theories of crime and criminality. It arranges theories in temporal sequence, from distal to proximal causes of crime, and is organised under three key headings: theories that focus on factors present at birth (human nature, heredity); theories that focus on factors that influence the offender over the lifespan (learning and development); theories that focus on factors present at the crime scene. The book emphasizes the connections among the different approaches, and demonstrates how, taken together rather than as rival explanations, they provide a more complete picture of crime and criminality. Psychological Criminology highlights the contributions that psychological theory can make to the broader field of criminology. It is essential reading to students, academics, researchers and practitioners in both criminology and forensic psychology"--